Effects of char chemical structure and AAEM retention in char during the gasification at 900C on the changes in low-temperature char-O2 reactivity for Collie sub-bituminous coal - Li, T.; Zhang, L.; Dong, Li; Wang, Shuai; Song, Y.; Wu, L.; Li, Chun-Zhu (Elsevier Ltd, 2017)
© 2017 Elsevier LtdThis study is focused on the effects of char structure and alkali and alkaline earth metallic (AAEM) species on the changes in char-O2 reactivity for a Western Australian Collie sub-bituminous coal. The char samples used in this study were acquired from the partial gasification of the sub-bituminous coal in a fluidised-bed/fixed-bed reactor in pure CO2, 15% H2O balanced with Ar and a mixture of 15% H2O and CO2 (balancing gas) at 900 °C. The structural features of the chars were characterised by FT-Raman spectroscopy. The concentrations of AAEM species in the chars were determined by inductively coupled plasma – optical emission spectroscopy. The O-containing structures in char that can cause resonance effects to give enhanced Raman intensity tend to improve the retention of AAEM species in char during the gasification at 900 °C. However, these O-containing structures do not necessarily ensue a high char-O2 reactivity at low temperature. While AAEM species in char would catalyse the char-O2 reactions, they are not sufficient to determine the char-O2 reactivity. The relative ratio of small to large aromatic ring systems in char, as reflected by the Raman spectroscopy, greatly influences the char-O2 reactivity. The sub-bituminous coal in this study does not behave in the same way as the brown coal in our previous studies in terms of the factors influencing the char-O2 reactivity.